Peningkatan SDM Melalui Keterampilan Desain Grafis Sebagai Peluang Usaha Ekonomis Produktif (UEP) Karang Taruna Desa Sokawera - Suliswaningsih Suliswaningsih; Andre Junianto; Aris Dwi Arianto (Madani : Indonesian Journal of Civil Society, 2020)
Tekad Sembada IX is a youth organization in the village of Sokawera, Cilongok, which was established in 1986. One of Karang Taruna Tekad Sembada IX's vision is to have a youth activity center called Karang Taruna Corner, where one of its activities is to create businesses in the field of digital printing. One of the skills needed is to make graphic designs to support these activities, therefore there is need for training to improve the ability of members of the organization. The purpose of community service is to provide knowledge and skills to members of Karang Taruna Tekad Sembada IX in Sokawera village, Cilongok by using Coreldraw software. Training materials include installation steps and the use of Coreldraw software to create banner and logo designs. The method used in this service activity is to provide training through the presentation and the use of Coreldraw software. The achievement of this dedication activity are the implementation of graphic design training with 10 participants who can take part in the training and the knowledge about graphic design using Coreldraw gained by the participant as a step to improve the human resources of Karang Taruna Tekad Sembada IX members in Sokawera village, Cilongok, Banyumas.